Morphophysiological and transcriptome analysis reveal that reprogramming of metabolism, phytohormones and root development pathways governs the potassium (K+) deficiency response in two contrasting chickpea cultivars - Ankit, Ankit; Singh, Ajeet; Kumar, Shailesh; Singh, Amarjeet (Frontiers in Plant Science, 2023)
Potassium (K+) is an essential macronutrient for plant growth and development. K+ deficiency hampers important plant processes, such as enzyme activation, protein synthesis, photosynthesis and stomata movement. Molecular mechanism of K+ deficiency tolerance has been partly understood in model plants Arabidopsis, but its knowledge in legume crop chickpea is missing. Here, morphophysiological analysis revealed that among five high yielding desi chickpea cultivars, PUSA362 shows stunted plant growth, reduced primary root growth and low K+ content under K+ deficiency. In contrast, PUSA372 had negligible effect on these parameters suggesting that PUSA362 is K+ deficiency sensitive and PUSA372 is a K+ deficiency tolerant chickpea cultivar. RNA-seq based transcriptome analysis under K+ deficiency revealed a total of 820 differential expressed genes (DEG’s) in PUSA362 and 682 DEGs in PUSA372. These DEGs belongs to different functional categories, such as plant metabolism, signal transduction components, transcription factors, ion/nutrient transporters, phytohormone biosynthesis and signalling, and root growth and development. RNA-seq expression of randomly selected 16 DEGs was validated by RT-qPCR. Out of 16 genes, 13 showed expression pattern similar to RNA-seq expression, that verified the RNA-seq expression data. Total 258 and 159 genes were exclusively up-regulated, and 386 and 347 genes were down-regulated, respectively in PUSA362 and PUSA372. 14 DEGs showed contrasting expression pattern as they were up-regulated in PUSA362 and down-regulated in PUSA372. These include somatic embryogenesis receptor-like kinase 1, thaumatin-like protein, ferric reduction oxidase 2 and transcription factor bHLH93. Nine genes which were down-regulated in PUSA362 found to be up-regulated in PUSA372, including glutathione S-transferase like, putative calmodulin-like 19, high affinity nitrate transporter 2.4 and ERF17-like protein. Some important carbohydrate metabolism related genes, like fructose-1,6-bisphosphatase and sucrose synthase, and root growth related Expansin gene were exclusively down-regulated, while an ethylene biosynthesis gene 1-aminocyclopropane-1-carboxylate oxidase 1 (ACO1) was up-regulated in PUSA362. Interplay of these and several other genes related to hormones (auxin, cytokinin, GA etc.), signal transduction components (like CBLs and CIPKs), ion transporters and transcription factors might underlie the contrasting response of two chickpea cultivars to K+ deficiency. In future, some of these key genes will be utilized in genetic engineering and breeding programs for developing chickpea cultivars with improved K+ use efficiency (KUE) and K+ deficiency tolerance traits.